WAIST TO STATURE RATIO AS A RISK FACTOR FOR DEVELOPMENT OF CARDIOVASCULAR DISEASES SERVERS IN A PUBLIC INSTITUTION OF HIGHER EDUCATION IN THE STATE OF PARANÁ (Fiep Bulletin - online, 2013)
Excess weight is already treated as a public health problem, in addition to body fat distribution is strongly related to coronary problems, so the aim of the study was to identify the values of WHtR employee of a public institution of higher education Paraná discriminating coronary risk factors. Study participants were 329 servers (135 teachers, 194 administrative staff) were measured weight, height, waist circumference (71.7 ± 14.9, 70.3 ± 9.0 kg; 168, 4 ± 9.2; 164.7 ± 9.0 cm, 86.7 ± 13.0, 87.7 ± 14.0 cm) respectively, were calculated WHtR and BMI (25.1 ± 4.3 kg/m2, 25.7 ± 4.48 kg / m2, 0.51 cm ± 0.7, 0.53 ± 0.8 cm). The servers did not show values above the recommended cutoff for WHtR, not being found values indicate that coronary risk, however it is suggested to conduct further studies investigating other variables, since BMI indicates overweight found.
Keywords: waist-to-height ratio; bmi; cardiovascular diseases